Analysis of the Effect of Provision of People's Business Loans on Farmers' Income in Bosar Maligas District, Simalungun Regency - Nanda Safitri Sinaga; Darwin Damanik; Pawer Darasa Panjaitan (Publikasi Indonesia, 2022)
This study aims to determine the effect of people's business credit on farmers' income in Bosar Maligas District, Simalungun Regency. This study uses a quantitative method with farmers receiving People's Business Loans in the Bosar Maligas sub-district, Simalungun Regency, amounting to 159 people. In this review, there were 30 farmer respondents who used People's Business Credit in Bosar Maligas District, Simalungun Regency. These results indicate that the people's business credit variable has a probability value greater than 0.05 and the regression coefficient shows a positive value. This means that the variable of people's business credit has no significant effect on the income of farmers in Bosar Maligas District, Simalungun Regency. Based on this, the hypothesis which states that people's business credit has a positive and significant effect on farmers' income in Bosar Maligas District, Simalungun Regency is rejected. Based on the results of testing and discussion of the influence of the independent variable in the form of People's Business Credit on Farmers' Income in Bosar Maligas Subdistrict, it is concluded that (1) People's Business Credit Variable has a positive and insignificant effect on Farmers' Income in Bosar Maligas Subdistrict, Simalungun Regency. (2) Test Results simultaneously declared that the People's Business Credit simultaneously influence positively and not significant to the Farmers' Income in the District SimalungunBosar Maligas .